Modelling species distribution of frogs (Anura:ranidae) in Sarawak using secondary data - Nurul Nazirah, binti Azizan (Universiti Malaysia Sarawak, UNIMAS, 2012)
Modelling species distribution of frogs in Sarawak (family: Ranidae) were conducted using secondary data collected from UNIMAS Zoological museum and Sarawak Biodiversity Centre (SBC). For this study, a total of eight species and 753 individuals of frogs from family Ranidae were detected at 16 surveyed localities in Sarawak. Generalized Linear Models (GLMs) using R software was used to analyze environmental variables that affecting the present distribution of each species detected at the surveyed localities, in which Akaike Information Criterion (AIC) used as model selection. In this study, seasonal rainfall variation has the lowest AIC value for distribution of Hylarana raniceps (110.605), while for Staurois guttatus and Hylarana picturata, disturbance effects of habitat type has affecting their distribution with AIC value of 61.812 and 44.163 respectively. Other than that, habitat type had influenced the distribution of Meristogenys phaeomerus (25.543) and Odorrana hosii (52.009). Habitat types, seasonal rainfall variation and disturbance effects have affecting the distribution of Hylarana baramica (32.904), Hylarana erythraea (25.519), and Meristogenys poecilus (26.539). Distribution maps of each species detected at surveyed localities were also presented.